Synthesis of a starch-composite magnetic material modified with polyethyleneimine for enhanced adsorption of diclofenac sodium, methyl orange, Amaranth, and hexavalent chromium - Jisuan Tan; Lingzhen Kong; Jingbo Fang; Xingtang Liang; Yanzhen Yin (Environmental Advances, 2024)
This study introduces Magnetic Starch (MAST), an innovative material designed for the efficient and rapid removal of water contaminants. MAST is synthesized by integrating polyethyleneimine and magnetic Fe3O4 nanoparticles into a starch composite. It exhibits a saturation magnetization of 7.3 emu/g and a functional surface area of 3.55 m² g−1. MAST's amine group density is 12.03 mmol/g, indicating a strong affinity for pollutants. Notably, MAST demonstrates exceptional adsorption capacities for various hazardous substances, including diclofenac sodium (620.51 mg g−1), methyl orange (470.85 mg g−1), amaranth (193.71 mg g−1), and hexavalent chromium (164.62 mg g−1). Thermodynamic studies reveal that the adsorption process is spontaneous and endothermic, with increased efficiency at higher temperatures, indicating suitability across various thermal conditions. MAST achieves rapid equilibrium within 20 minutes, conforms to pseudo-second-order and Langmuir models, and exhibits selective adsorption in complex matrices. These attributes underscore its potential for broad environmental remediation applications. Furthermore, MAST can be easily separated from water using magnets and retains 60 % of its effectiveness after five usage cycles, endorsing its feasibility for repeated use.